The Influence of Competence and Job Satisfaction on the Performance of Employees in Indonesian Educational and Professional Development Institutions (LP3I) Through Organizational Commitment as a Mediation Variable - ZUNIZAR, Rofi; RIBHAN, Ribhan; MARDIANA, Nova (PT Keberlanjutan Strategis Indonesia, 2023)
Research was conducted to determine the effect of competence on employee performance and job satisfaction on performance. Employees, competence on organizational commitment, job satisfaction on organizational commitment, and organizational commitment mediate between competence on employee performance and organizational commitment as a mediating variable for job satisfaction on employee performance. The research method is the Structural Equations Model with the SEM-AMOS analysis tool. This research is quantitative, with a sample size of 230 using a purposive sampling method. The empirical findings are that competency is positive and significant to employee performance. Job satisfaction is positive and significant on employee performance. Competence is positive and significant towards organizational commitment. Job satisfaction is positive and significant on organizational commitment, as well as positive and significant organizational commitment on employee performance, and the influence of competency on employee performance is indirectly mediated by organizational commitment, which is positive and significant. From the results of the research that has been carried out, the statement obtained using descriptive analysis and the lowest score in this research is recommended for LP3i that communication competence between colleagues needs to be improved to have a good impact on employee performance.